Women Security Using Android App - A. Deshkar, Shivani; M. Laxane, Shraddha; M. Lendhare, Payal; N. Khade, Poonam (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Now-a-days women harassment is increasing and women and children safety is a big question mark. To overcome this problem, this paper explores the IOT concepts such as measuring the body temperatures, heart beat rates/pulse rates by sensors to monitor their conditions and alerts nearby location police station or relatives. Since, there are some web or mobile applications for women safety and emergencies, it does not work at all situations. The lady cannot stay on the gadget at all the time. Instead, she could be monitored by wearing smart watches, etc. It could be accessed by wireless technologies like GPS, GSM, GPRS, and Wi-Fi and monitored by nearby devices.